Obesity in adults: a review - Gul, Shandana; Adeel, Mehreen (International Journal of Research in Medical Sciences, 2025)
Obesity is a chronic complex disease that is caused by excessive fat deposits in the human body, and it is considered as one of the major causes of health impairment. It increases the risk of type 2 diabetes and heart diseases in addition to affecting bones and reproduction system that can increase the risk of certain types of cancer. Furthermore, it has a major impact on the quality of living, such as sleeping disorder or physical movement. Its early diagnostic procedure involves a regular monitoring of the human’s body mass index (BMI): weight (kg)/height2 (m2). The body mass index is an initial surrogate marker to confirm fatness and waist circumference that helps to diagnose obesity. It is an emerging and growing public health issue in the Western world as well as in the Middle East countries. More specifically, obesity in Qatar is the focus in this article which is among the top-ranked obese countries with a high obesity rate among its population and only a limited number of studies focused on the systematic identification of potential risk factors using multimodal datasets. This article aims to focus on the main causes of obesity, its diagnosis, management approach and pharmacological and non-pharmacological treatments.